Electrical stimulation therapy of the lower oesophageal sphincter for refractory gastro‐oesophageal reflux disease – interim results of an international multicentre trial. Issue 5 (8th July 2015) - Kappelle, W. F. W.; Bredenoord, A. J.; Conchillo, J. M.; Ruurda, J. P.; Bouvy, N. D.; van Berge Henegouwen, M. I.; Chiu, P. W.; Booth, M.; Hani, A.; Reddy, D. N.; Bogte, A.; Smout, A. J. P. M.; et al.
Summary Background A previous single‐centre study showed that lower oesophageal sphincter electrical stimulation therapy (LES‐EST) in gastro‐oesophageal reflux disease (GERD) patients improves reflux symptoms and decreases oesophageal acid exposure. Aim To evaluate safety and efficacy of LES‐EST in GERD patients with incomplete response to proton pump inhibitors (PPIs) in a prospective, international, multicentre, open‐label study. Methods GERD patients, partially responsive to PPIs, received LES‐EST. GERD health‐related quality of life (GERD‐HRQL), daily symptom diaries, quality of life scores, oesophageal acid exposure, and LES resting and residual pressure were measured before and after initiation of LES‐EST. Stimulation sessions were optimised based on residual symptoms and oesophageal acid exposure. Results Forty‐four patients were enrolled and 6‐month data from 41 patients are available. Hiatal repair was performed in 16 patients. One device‐related, one procedure‐related and one unrelated severe adverse event were reported. GERD‐HRQL improved from 31.0 (IQR 26.2–36.8) off‐PPI and 16.5 (IQR 9.0–22.8) on‐PPI to 4 (IQR 1–8) at 3‐month and 5 (IQR 3–9) at 6‐month follow‐up (P < 0.0001 vs. on‐ and off‐PPI). Oesophageal acid exposure (pH < 4.0) improved from 10.0% (IQR 7.5–12.9) to 3.8% (IQR 1.9–12.3) at 3 months (P = 0.0027) and 4.4% (IQR 2.2–7.2) at 6 months (P < 0.0001). Conclusions These interim results show an acceptable safety record of LES‐EST to date, combined with good short‐term efficacy in GERD patients who are partially responsive to PPI therapy. A remarkable reduction in regurgitation symptoms, without the risk of intervention‐requiring dysphagia may prove to be an advantage compared with other anti‐reflux procedures. ClinicalTrials.gov Identifier: NCT01574339.